Pengenalan Makanan Pendamping ASI (MPASI) melalui Edukasi dan Demo Masak untuk Pencegahan Stunting selama Periode Golden Age 1000 Hari Kehidupan Anak di Kelurahan Rejosari - Nadilah Putri Sani; Yunni Safitri; Yulisma Yulisma; Dwi Riska Amiroh; Tengku Ilma Nadila; Indah Rahma Yena; Tengku Manawa Salwa (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
The 1000 day period of life is a golden period to form a child's growth. The nutrition that children receive during the 1000 day period of life can affect the child's ability to learn and work so that a healthy generation is formed in the long term. At the age of 6 months, the baby's need for energy and nutrition begins to increase so that it cannot be fulfilled only with breast milk, so complementary food ASI (MPASI) is needed. If complementary foods are not introduced from about 6 months or inappropriately, they can be a risk factor for stunting. The method used in this community service is to provide education and cooking demonstrations on a healthy menu of complementary foods for ASI (MPASI), by doing hands-on practice. The results obtained from this activity are that mothers understand complementary foods and make better ones by choosing quality ingredients that can increase the baby's appetite by being more innovative and creative.